Penerapan Model Pembelajaran Problem Based Learning berbantu Media Index Card Match untuk Meningkatkan Minat dan Hasil Belajar Siswa Materi Wujud Benda - Silviana Nur Hamidah; Singgih Bektiarso; Subiki Subiki (Universitas Muhammadiyah Enrekang, 2022)
This study aims to increase students' interest and learning outcomes in material objects by applying a problem based learning model with the help of index card match media, describing the increase in student interest and learning outcomes in material objects after applying the problem based learning assisted learning model. index card match media. This research is a classroom action research conducted with 2 cycles. The research subjects were the second grade students of SDI Darul Musthofa, totaling 8 students in the odd semester of the 2021/2022 academic year. The results showed an increase in student interest and learning outcomes after applying the problem based learning model with the help of index card match media.